Learning Strategy for Students’ Entrepreneurial Spirit through Students’ Cooperation (KOPMA) - Meiwatizal Trihastuti; Aim Abdulkarim; Endang Danial; Acep Supriadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
At present, a number of contemporary skills become crucial for students in learning process, especially the entrepreneurship skill. This article aimed to identify the students’ learning strategy on entrepreneurial spirit through student’s cooperation (KOPMA). This study was descriptive qualitative study that involved five student’s cooperation (KOPMA) in 4 universities. This study has resulted that KOPMA has become a media in forming entrepreneurial spirit for students. Besides, the learning strategy was carried out through: 1) dividing a time-set between academic learning and cooperation (KOPMA); and 2) bravery to take any risk in cooperation (KOPMA). This learning strategy was intended to instill and develop students’ entrepreneurial spirit. Keywords: Learning Strategy, Entrepreneurial Spirit, Entrepreneurship